Spatiotemporal Land Cover Dynamics and Their Implications For Watershed Quality in the Minraleng Sub-Watershed, Indonesia - Nisa Nur Ramadhani; Wahyuni Wahyuni; Putri Fatimah Nurdin; Muhammad Daud (Forestry Department, University of Muhammadiyah Makassar, 2026)
Land use change is a key indicator of environmental dynamics in watershed ecosystems, particularly in areas experiencing increasing land use changed. This study aims to analyze spatiotemporal land use changes and assess watershed quality based on permanentvegetation cover in the Minraleng Sub-Watershed, Indonesia. Sentinel-2 Level-2A satellite imagery from 2017, 2020, and 2023 was processed and analyzed using a GIS-based overlay approach. Image preprocessing included radiometric correction, band combination, clipping, and on-screen digitization, followed by ground validation using GPS. Classification accuracy was evaluated using confusion matrix and kappa statistics. The results indicate that the Minraleng Sub-Watershed is predominantly covered by primary dryland forest. Forest cover declined by 0.95% between 2017 and 2020 but slightly increased by 0.16% from 2020 to 2023. Watershed quality based on Permanent Vegetation Cover (PVC) remained in the good category, with values of 61% in 2017, 60% in 2020, and 61% in 2023. Classification accuracy was high, with kappa values ranging from 92.25% to 96.43%. These findings provide important insights for sustainable watershed management and strategies to mitigate land degradation risks. Despite the fact that PVC is still classified as being in a good category, the continuous decline in forest cover indicates a growing threat to watershed sustainability, especially in terms of maintaining hydrological functions, regulating streamflow, and preserving the ecological integrity of the watershed.